ChemInform Abstract: Asymmetric α‐Amination Reaction of Alkenyl Trifluoroacetates Catalyzed by a Chiral Phosphine—Silver Complex. Issue 31 (5th August 2014) - Yanagisawa, Akira; Miyake, Ryoji; Yoshida, Kazuhiro
Abstract A novel catalytic asymmetric α‐amination of alkenyl trifluoroacetates is developed that allows the synthesis of various optically active α‐hydrazino ketones with enantioselectivities up to 97% e.e.